FUZZY EXPERT AIR TEMPERATURE CONTROL SYSTEM IN SHOPPING AND ENTERTAINMENT CENTER PREMISES - Михайленко, В.С.; Шевченко, Т.І.; Стукалов, С.А.; Зуй, О.М.; Мартинович, Л.Я. (Військовий інститут Київського національного університету імені Тараса Шевченка, 2023)
Abstract The article presents the stages of developing a fuzzy expert system for the operator of a heating point of a shopping and entertainment center. The principle of operation of the air heating system of the mall is shown, implemented using computer-integrated control with a SCADA system. For the effective operation of the air temperature control system in different areas of the mall, functions for belonging to comfort zones have been developed in terms of visitors and the requirements of sanitary standards. It is indicated that typical air temperature stabilization controllers cannot always provide the desired mode due to the influence of a large number of uncontrolled disturbances on the control system. In this case, in the absence of additional blocks for adapting control algorithms, it becomes expedient to remotely control the operator using a mnemonic diagram of the ventilation process. And to improve the efficiency of the process of remote control of thermal equipment, an expert system was proposed that implements the algorithm of I. Mamdani, to control the coolant flow valves. The controller receives information from the outdoor air and air temperature sensors in the control area of the mall. After processing the signals from the sensors, the controller transmits information to a computer with an expert system. Depending on the temperature and season of the year, the program calculates the optimal position of the valve (in percentage of stroke) for the flow rate of the coolant and recommends installing it to the operator. Also, it is shown that in the process of developing a fuzzy expert system, it is recommended to choose the Gaussian type of membership functions; minimal number of terms - sets - three functions of dependency; weight coefficient of each rule in the knowledge base is the same and equal to 100; the method of defasification is the method of the center of gravity. It is indicated that the introduction of expert advice to operators can also lead to a reduction in the response time to emergency situations up to 90% increase in the reliability of the equipment as a whole.

У статті подано етапи розробки нечіткої експертної системи для оператора теплового пункту торгово-розважального центру. Показано принцип роботи системи повітряного опалення ТРЦ, що реалізується за допомогою комп'ютерно-інтегрованого керування зі SCADA – системою. Для ефективної роботи системи управління температурою повітря у різних зонах ТРЦ розроблено функції належності зон комфорту з погляду відвідувачів та вимог санітарних норм. Вказано, що типові регулятори стабілізації температури повітря не завжди можуть забезпечити заданий режим через вплив великої кількості неконтрольованих збурень на систему управління. У такому випадку за відсутності додаткових блоків адаптації алгоритмів керування доцільним ставати дистанційне керування оператором за допомогою мнемосхеми процесу вентиляції. І для підвищення ефективності процесу дистанційного регулювання тепловим устаткуванням запропоновано експертну систему, що реалізує алгоритм І. Мамдані, з управління клапанами витрати теплоносія. Контролер отримує інформацію від датчиків температури зовнішнього повітря та повітря в зоні контролю ТРЦ. Після обробки сигналів від датчиків контролер передає інформацію на комп'ютер з експертною системою. Залежно від значень температури та пори року програма розраховує оптимальне положення клапана (у відсотках ходу) витрати теплоносія та рекомендує встановити його оператору. Також, показано, що у процесі розробки нечіткої експертної системи рекомендується обирати гаусівський тип функцій належності; мінімальна кількість терм – множин – три функції належності; вагові коефіцієнти кожного правила в базі знань однакові та дорівнюють 100; метод дефазифікації – метод центру тяжіння. Вказано, що введення експертних порад операторам також може призвести до зниження часу реакції на позаштатні ситуації до 90% підвищення надійності роботи обладнання загалом.
НЕЧІТКА ЕКСПЕРТНА СИСТЕМА ДЛЯ КЕРУВАННЯ ТЕМПЕРАТУРОЮ ПОВІТРЯ У ПРИМІЩЕННЯХ ТОРГОВЕЛЬНО-РОЗВАЖАЛЬНОГО ЦЕНТРУ
Keywords: нечітка експертна система; температура повітря; повітряне опалювання; оператор; fuzzy expert system; air temperature; air heating; operator